ENVIRONMENTAL STABILITY OF THE WATER BASIN LANDSCAPE AS ONE OF THE FACTORS OF THE HYDRECOSYSTEM STATE FORMATION (ON THE EXAMPLE OF THE RIVER STYR) - Voznіuk, Nataliya; Kopylova, Olga; Stetsiuk, Liudmyla (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The main attention is focused on the need to study the stability of the hydroecosystem basin landscape as one of the stages of a comprehensive assessment of the watercourse state. The calculation of the CESL has been carried out and the corresponding stability of the landscape of the areas located within the Styr river basin has been determined.